Development of supervibration-photocatalytic reactor for treatment of lignin and 2,4-dichlorophenol in pulp and paper mill wastewater - Suchanya Thongkrua (Chulalongkorn University, 2013)
Thesis (Ph.D)--Chulalongkorn University, 2010